Penerapan Media Permainan Dakon Untuk Meningkatkan Hasil Belajar Matematika Pada Materi Operasi Hitung Bilangan Cacah Di Kelas III SDN 194/IX Matra Manunggal - Asisah Kurniati; Fauzi Fadliansyah (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
This research was motivated by the low level of students' skills when performing whole number calculation operations. One alternative that can be implemented in learning improvement procedures is to use dakon game media. Dakon game media can help and make it easier for students to interpret mathematical calculation concepts. The aim of this research is to improve mathematics learning outcomes regarding the operation of calculating whole numbers using the dakon game media in class III at SDN 194/IX Matra Manunggal. The approach used in this research is a qualitative approach which is researched using the type of classroom action research. The subjects for this learning improvement were 11 class III students at SDN 194/IX Matra Manunggal. Data collection is carried out using tests, observations and documentation. In this learning improvement research, the data that has been collected will be analyzed using two analytical techniques, namely quantitative and qualitative data analysis. The research results show that student learning outcomes in cycle 1 with an average score of 70 in the Good category, and a completion percentage of 63.64%. In cycle 2, an average score of 77.27 was obtained in the good category with the student learning completion level reaching 90.91%. Therefore, it can be synthesized that the process of implementing the dakon game media can improve mathematics learning outcomes in whole number counting operation material for class III SDN 194/IX Matra Manunggal.